Model Orientasi Relasi antara Konsumen dengan Penyedia Jasa Maskapai Penerbangan Domestik - Utami, Christina Whidya; Musanto, Trisno (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2004)
Since opening the opportunity of commercial air transport operation permit in Indonesia in the year 1999, pushing to born the various new air transport in Indonesia. Emerge the well-unbalanced between supply and demand, so that some air transport firm given on a very light emulation condition. On the other side, consumer remain to wish fulfilling standard of safety and satisfying service quality.